Analisis Pengaruh Penjualan, Biaya Produksi dan Biaya Operasi Terhadap Laba Wajar PT. Ogawa Indonesia dari Afiliasinya - Simatupang, Ricardo; Siagian, Arifin (Pasca Sarjana Universitas Satya Negara Indonesia, 2018)
The purpose of this study is to determine the effect of sales, production cost and operating expenses on operating profit indicator as an arm’s length measurement. The study in PT. Ogawa Indonesia. Sampling technique used is purposive sampling. The sample of this study is sales, cost of goods sold as production cost, operation expenses and opera ting profit that is used to measure of PT. Ogawa Indonesia’s operating profit indicator in the year 2012-2017. The dependent variable (Y) in this study is operating profit. The independent variable (X) include: sales (X1), cost of goods sold (X2) and opera tion expenses (X3). Methods of data analysis used is double linear regression with IBM SPSS statistical program 24.The results of this study indicate that sales positive and significant effect on the operating profit indicator of the test results tcount 18,100 > 2,086 ttable,, variable production cost significant and positive effect on operating profit indicator of the test results tcount 17,824>2,086 ttable, and variable operation expenses significant and positive effect on operating profit indicator of the test result tcount 6,008>2,086 ttable,. Meanwhile the collective effect of sales, production cost and operation expenses on the operating profit indicator of the test results fcount 138,762>3,07 fttable.Other than statistical test above, the operating profit of the tested company was also tested by using TNMM method as most appropriate method for the company and at the end the PLI of the tested company indicate arm’s length against its comparable companies.